Unerupted maxillary central incisors: a case report and review of the literature - O. O. Orenuga; J. O. Eigbobo (Nigerian Dental Journal)
Missing or unerupted central incisors in a child can have a major impact on oro-facial aesthetics. This may be a source of great psychological concern to child and parents by virtue of its prominent anterior location. Non-eruption could be due to hereditary and local environmental factors. Surgical and/or orthodontic intervention is often required in the management of the condition especially after six months since the eruption of the contra lateral tooth. In this report, a nine year old boy presented with unerupted maxillary right central and lateral incisors. The management involved clinical, radiographic and orthodontic assessment. A diagnosis of hyperplastic gingivae preventing eruption of the incisors was made. Removal of the obstruction and exposure of the crowns of the teeth resulted in their spontaneous eruption and subsequent alignment in the maxillary arch. It is concluded that teeth which have not erupted six months after their normal eruption time be examined radiographically. Early removal of causative factors leads to better prognosis This mixed dentition anomaly of tooth eruption was conservatively managed by paedodontist.